Propaganda Feminisme di Era Society 5.0: Telaah Pandangan Sensasional Perempuan Gen Z di Tiktok dalam Perspektif Islam - Amril; Azhar, Anang Anas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the phenomenon of feminist propaganda on the TikTok platform as a representation of the dynamics of Gen Z women's identity and expression in the era of Society 5.0. Through descriptive qualitative methods and content analysis, this study examines feminist narratives that appear in video content and accompanying digital interactions. The results of the study show that TikTok is not only an entertainment space, but also a discursive arena that forms a collective awareness of gender equality issues. However, in practice, most of the narratives circulating have shifted from the essence of inclusive feminism to ideologically biased forms of sensational expression, such as reverse sexism, patriarchal generalizations, and the imposition of moral standards. This phenomenon creates tension between the values of digital freedom of expression and the principle of equality in Islam. This research recommends the need for digital literacy based on spirituality and manners so that the digital space is not only a vehicle for ideological struggle, but also a means of da'wah that builds a just civilization. Thus, feminist propaganda needs to be critically reviewed so that it does not shift into value extremism that is counterproductive to the ideals of gender justice in an Islamic perspective.